Membangun Relasi untuk Meraih Popularitas Grup Musik Soegi Bornean - Saputra, Al Ghiffari Bintang; Indrayani, Heni (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2024)
The situation that shows Soegi Bornean can gain popularity quickly even though the condition of the music industry in Semarang is still inferior to several other cities, indicates that the band applies public relations strategies with external parties to improve its image which has an impact on popularity. So, the formulation of this problem is to describe these indications using John A. Ledingham's relationship management theory. The research method used is qualitative with case studies. The results showed that Soegi Bornean achieved popularity in a short time because it carried out relationship management activities with external parties, such as aggregators and fanbases. In its implementation, Soegi Bornean applies the principles of relationship management and SMARTS model very well until have a positive quality. Therefore, it has an impact on increasing Soegi Bornean's popularity where a public recognises Soegi Bornean as a music group that has physical attractiveness, attractiveness of work, positive personnel characteristics, and is active in the community.